An Investigation Into The Use Of Conceptual Metaphors In Business Articles (Đại học Ngoại ngữ, Đại học Đà Nẵng, 2025)
The purpose of this research is to examine the frequency of usage of various types of Conceptual Metaphors (CMs) in 40 business newspapers published by The Economist. Data on the quality of CMs was collected and analysed using both quantitative and qualitative methods. The study employed mapping techniques to identify the source and target domains of metaphors and subsequently analysed their meanings. The findings identified three types of CMs - structural, ontological, and orientational metaphor - in business journalism, as defined by Lakoff’s and Johnson’s Conceptual Metaphor Theory. The results indicated that ontological metaphor was the most prevalent type, with 170 instances accounting for 42.5% of the total, followed by structural and orientational metaphors. Additionally, the study offers applicability of teaching and learning conceptual metaphors and provides suggestions for further research into CMs in business and economics. The research concluded that the use of metaphors in journalism helps readers in visualising concepts, enhances the persuasiveness of writers, and improves memorability for both parties.